Directly observing household food waste generation using composition audits in a Canadian municipality. (November 2021) - Parizeau, Kate; von Massow, Mike; Martin, Ralph C.
Highlights: Detailed observational data is important for household food waste measurement. Average household food waste per capita was 1.64 kg per week. Avoidable food waste per capita was 1.05 kg per week (64% of total). Most total and avoidable food waste was fruits and vegetables. Household composition, beliefs, and lifestyles may impact food waste generation. Abstract: This study complements a previous study that combined household survey data with weights of curbside separated organics in the residential sector (Parizeau et al., 2015). Our findings reinforce the need for the collection of detailed observational data in household food waste audits. We revisited some households from the original study and a new set of households in order to conduct compositional audits on all three streams of waste, and to combine these results with survey data. In the compositional audits, we observed an average food waste per capita of 1.64 kg per week, and avoidable food waste per capita of 1.05 kg per week. Overall, 64% of wasted food was avoidable. The highest proportions of total and avoidable food waste came from fruits and vegetables (63%; 59%), followed by bread products (14%; 22%). Combining the compositional audits with survey data, we confirmed some of the behavioural and attitudinal patterns assessed in our previous study, including that household composition, food awareness, waste awareness, and convenience lifestyles may impact household food waste generation rates. Individual household audits provide greater insight into food waste generation than do curbside weights.